Improving vitamin A consumption in vulnerable households. Viable Sweetpotato Technologies in Africa (VISTA) Mozambique. Research Brief 02 - Jogo, W.; Bocher, T.; Andrade, M.I. (International Potato Center, 2019)
The VISTA Mozambique project contributes to improved nutrition, food security and incomes of smallholder farming families through increased production and better utilization of nutritious OFSP varieties. The project has been funded by USAID under the Feed the Future program with US$6.25 million over 5 years (2014-2019). The project’s targets were to reach 65,000 households directly and 160,000 households indirectly by 2019.